Efforts to Improve Writing Ability Poetry Through Implementation of Learning Methods Image Streaming Student Class V - Puji Handayani; Missriani; Muhammad Ali (Global Action and Education for Society, 2025)
This study aims to: (1) Determine the ability of fifth grade students of SD Negeri 24 Sembawa to write poetry through the application of the image streaming learning method; (2) Determine the extent of the increase in the ability to write poetry of fifth grade students of SD Negeri 24 Sembawa through the application of the image streaming learning method. This type of research is an action research that is carried out in 2 cycles and each cycle consists of two meetings with a time allocation of 2x35 minutes for each meeting. This research was conducted in fifth grade students of SDN 24 Sembawa, Banyuasin Regency. The data collection technique was carried out through poetry writing test activities. The results of this study indicate that: (1) Through the application of the image streaming learning method, the ability of fifth grade students of SDN 24 Sembawa to write poetry can be improved; (2) The percentage increase in the ability of fifth grade students of SDN 24 Sembawa to write poetry from the implementation of the test in cycle I to cycle II is 14.32%.